Comorbidities in chronic pediatric peritoneal dialysis patients: a report of the international pediatric peritoneal dialysis network - Neu, Alicia M.; Sander, Anja; Schaefer, Franz (Peritoneal dialysis international, 2012)
Background, objectives, and methods: Hospitalization and mortality rates in pediatric dialysis patients remain unacceptably high. Although studies have associated the presence of comorbidities with an increased risk for death in a relatively small number of pediatric dialysis patients, no large-scale study had set out to describe the comorbidities seen in pediatric dialysis patients or to evaluate the impact of those comorbidities on outcomes beyond the newborn period. In the present study, we evaluated the prevalence of comorbidities in a large international cohort of pediatric chronic peritoneal dialysis (CPD) patients from the International Pediatric Peritoneal Dialysis Network registry and began to assess potential associations between those comorbidities and hospitalization rates and mortality. Results: Information on comorbidities was available for 1830 patients 0 - 19 years of age at dialysis initiation. Median age at dialysis initiation was 9.1 years [interquartile range (IQR): 10.9], median follow-up for calculation of hospitalization rates was 15.2 months (range: 0.2 - 80.9 months), and total follow-up time in the registry was 2095 patient-years. At least 1 comorbidity had been reported for 602 of the patients (32.9%), with 283 (15.5%) having cognitive impairment; 230 (12.6%), motor impairment; 167 (9.1%), cardiac abnormality; 76 (4.2%), pulmonary abnormality; 212 (11.6%), ocular abnormality; and 101 (5.5%), hearing impairment. Of the 150 patients (8.2%) that had a defined syndrome, 85% had at least 1 nonrenal comorbidity, and 64% had multiple comorbidities. The presence of at least 1 comorbidity was associated with a higher hospitalization rate [hospital days per 100 observation days: 1.7 (IQR: 5.8) vs 1.2 (IQR: 3.9), p = 0.001] and decreased patient survival (4-year survival rate: 73% vs 90%, p < 0.0001). Conclusions: Nearly one third of pediatric CPD patients in a large international cohort had at least 1 comorbidity, and multiple comorbidities were frequently reported among patients with a defined syndrome. Preliminary analysis suggests an association between comorbidity and poor outcome in those patients. As this powerful international registry matures, further multivariate analyses will be important to more clearly define the impact of comorbidities on hospitalization rates and mortality in pediatric CPD patients.